Enhancing Choices Regarding the Administration of Insulin Among Patients With Diabetes Requiring Insulin Across Countries and Implications for Future Care - Mardare, Ileana; Campbell, Stephen M.; Meyer, Johanna C.; Sefah, Israel Abebrese; Massele, Amos; Godman, Brian (Frontiers in Pharmacology, 2022)
There are a number of ongoing developments to improve the care of patients with diabetes across countries given its growing burden. Recent developments include new oral medicines to reduce cardiovascular events and death. They also include new modes to improve insulin administration to enhance adherence and subsequent patient management thereby reducing hypoglycaemia and improving long-term outcomes. In the case of insulins, this includes long-acting insulin analogues as well as continuous glucose monitoring (CGM) systems and continuous subcutaneous insulin infusion systems, combined with sensor-augmented pump therapy and potentially hybrid closed-loops. The benefits of such systems have been endorsed by endocrine societies and governments in patients with Type 1 diabetes whose HbA1c levels are not currently being optimised. However, there are concerns with the low use of such systems across higher-income countries, exacerbated by their higher costs, despite studies suggesting their cost-effectiveness ratios are within accepted limits. This is inconsistent in higher-income countries when compared with reimbursement and funding decisions for new high-priced medicines for cancer and orphan diseases, with often limited benefits, given the burden of multiple daily insulin injections coupled with the need for constant monitoring. This situation is different among patients and governments in low- and low-middle income countries struggling to fund standard insulins and the routine monitoring of HbA1c levels. The first priority in these countries is to address these priority issues before funding more expensive forms of insulin and associated devices. Greater patient involvement in treatment decisions, transparency in decision making, and evidence-based investment decisions should help to address such concerns in the future.